2005
DOI: 10.1080/10715760500097906
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of quinone redox cycling by ascorbate induces a caspase-3 independent cell death in human leukaemia cells. Anin vitrocomparative study

Abstract: Since the higher redox potential of quinone molecules has been correlated with enhanced cellular deleterious effects, we studied the ability of the association of ascorbate with several quinones derivatives (having different redox potentials) to cause cell death in K562 human leukaemia cell line. The rationale is that the reduction of quinone by ascorbate should be dependent of the quinone half-redox potential thus determining if reactive oxygen species (ROS) are formed or not, leading ultimately to cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
72
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 20 publications
9
72
2
1
Order By: Relevance
“…Figure 6). A caspase-3 independent cell death was previously observed in leukaemia cells after VK3 -AA treatment (Verrax et al, 2005). This can be reconciled with the notion that peroxidation of the plasma membrane of cells may favour unregulated increase in intracellular levels of calcium as previously observed (Sakagami and Satoh, 1997), which, along with thiol oxidation, may result in mitochondrial destabilisation.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Figure 6). A caspase-3 independent cell death was previously observed in leukaemia cells after VK3 -AA treatment (Verrax et al, 2005). This can be reconciled with the notion that peroxidation of the plasma membrane of cells may favour unregulated increase in intracellular levels of calcium as previously observed (Sakagami and Satoh, 1997), which, along with thiol oxidation, may result in mitochondrial destabilisation.…”
Section: Discussionsupporting
confidence: 67%
“…An antagonistic interaction was found for the combination of a-TOS and VK3, whereas AA did not exert any effect when combined with a-TOS. As previously described (De Loecker et al, 1993;Jamison et al, 1996;Verrax et al, 2005;Tareen et al, 2008;Beck et al, 2009) and also observed in this study, an efficient synergistic effect on cell viability was observed for the pro-oxidant mixture containing pharmacological doses of AA and a redox-active compound such as menadione (VK3), (c.f. Figure 2).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In summary, ER homeostasis is a fragile equilibrium, which can be modulated by dysregulation of calcium or oxidative/reductive balance, features previously associated with oxidative stress. However, studies of the links between these factors are scarce.We and others have shown that the association of ascorbate and menadione is an H 2 O 2 -generating system that results in necrosis-like cell death in a wide variety of cancer cell types [29][30][31][32][33][34][35] including MCF-7 cells (a human breast derived cell line), and that loss of calcium homeostasis appeared to be a major factor in the cytotoxicity [36]. The aim of the present study was to investigate the role of disruption of calcium homeostasis and a potential involvement of ER stress in the mechanisms leading to cancer cell death from an oxidative …”
mentioning
confidence: 99%